A ARTETERAPIA COMO RECURSO EDUCACIONAL PARA O ENSINO MÉDIO: UMA PROPOSTA INTERDISCIPLINAR - Matana, Cristiano (2023)
This research addressed the theme of art therapy as an educational resource for high school: an interdisciplinary proposal. The research carried out is characterized as exploratory and descriptive with a qualitative approach. The objective of the study was to understand how art therapy can contribute to the education of high school students. Data collection was carried out from 2021 to 2023. First, a bibliographical research was carried out in national bibliographic materials: books, articles, documentary sources, dissertations and theses. The following electronic databases were used: CAPES Portal, Scielo, Bireme, Pepsic and Google Scholar. The method used for the analysis and treatment of the bibliographic material collected was Content Analysis by Laurence Bardin. In the second moment of the research, an educational proposal in art therapy was elaborated, with an interdisciplinary bias, to be applied in the context of high school. The proposal was organized in workshops, structured from four modalities, based on the language of the arts: plastic, sound, literary, dramatic, corporal. As for the results of the first stage of the research, it was observed in the scientific literature a scarcity of bibliographic contents related to the subject studied. Not because the theme was of little relevance, but, due to the few findings in researched authors, attention was paid to reduced contributions with a co-relation between art therapy, education and secondary education. The second stage of this research presented, through the educational proposal elaborated by the researcher, results of a collaborative nature, since it is understood that art therapy can fill a gap in the education of young people in high school, through actions of health promotion and prevention mental health, so necessary in this complex phase of life. In this sense, art therapy, if well developed and worked on at school, considering one of the highlighted points, could come to help students in their integral human development, due to the creative and transformative potential present in art. This, therefore, has become an excellent auxiliary tool in understanding your internal world. A fact that allows, among other factors, the increase of their self-esteem, autonomy, as well as a healthy relationship with others and with the environment. In relation to the young student's internal world, art therapy was highlighted in the power that art has to help in their education and transformation. The rich symbolic contents and processes developed through art therapy activities can help young people learn to dialogue first with themselves, favoring self-knowledge and healthy personality development. In this way art therapy is constituted, it is possible to think about its humanizing and therapeutic effects for students. Humanizing insofar as it leads the subject to become more complete, mature and responsible for himself, for the other and for the environment in which he lives. Therapeutic, because the subject develops psychologically in a more integrated, balanced and self-regulated way, both affectively and emotionally.